Design and performance of a recirculating aquaculture system for oyster larval culture. (25th May 2017) - Qiu, Tianlong; Qi, Jianfei; Zheng, Jimeng; Liu, Ying
Abstract: The major objective of this study was to introduce a newly designed recirculating aquaculture system (RAS) for oyster ( Crassostrea angulata ) larval culture. The system includes a culture tank, a suspended circular inlet‐pipe, an upwelling aeration pipe, combined "banjo" sieves and a bioreactor chamber containing microalgae life keeping installation. The system was designed to resolve three problems: (i) stranding of larvae caused by water level changes and aeration, (ii) physical clogging of the screens and also (iii) deterioration of diet microalgae. The culture tank, "banjo" sieve size, water flow rate and light intensity for maintaining microalgae activity were all designed according to the pattern of larval movement and feeding behaviour. Results of this study showed the best average SGR for larval length was 6.36%/d (9.5 μm/d) and survival rate was 80%, with initial rearing density of 50 larvae/ml, indicating the problems above were fully resolved. Consequently, the system is fit for larval culture in mass production of oysters.